2019
DOI: 10.31557/apjcp.2019.20.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Evaluation of Ki-67 and Comparison with Clinicopathologic Factors in Breast Carcinomas

Abstract: Background: Patients primarily received tamoxifen based on their menopausal status due to the lack of immunohistochemistry. A recent study has shown that hormonal receptors were not correlated with menopausal status, and thus, indicating that they present limited therapeutic and prognostic significance in breast cancer management. This study aimed to evaluate Ki-67 value and analyze its association with clinicopathologic parameters in breast cancer patients. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 36 publications
4
20
0
Order By: Relevance
“…In our study, cases with ER negative or PR negative status had higher mean Ki-67 scores. Our results are in accordance with those revealed by some others that investigated Ki-67 as a continuous variable in breast cancer [ 40 , 42 , 46 , 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, cases with ER negative or PR negative status had higher mean Ki-67 scores. Our results are in accordance with those revealed by some others that investigated Ki-67 as a continuous variable in breast cancer [ 40 , 42 , 46 , 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…This result was similar to other previous studies done by Ayad et al. [18] ; Soliman et al [19] ; Rakha et al [20] ; Pierga et al [21] ; and Aman et al [22] . In our study, 49 (61.25%) cases have tumor-size 2 to 5 cm, 22(27.50%) cases have tumor, size >5 cm, 9 (11.25%) cases have tumor-size less than 2 cm.…”
Section: Discussionsupporting
confidence: 93%
“…Combination of chemotherapy with immunotherapy, as in this study, has also been shown by previous studies [8][9][10] to enhance survival of patients.…”
Section: Discussionsupporting
confidence: 81%
“…Immunotherapy has proved to be of great advantage in the treatment of metastatic breast carcinoma, especially when combined with chemotherapy [7][8][9][10], as well as in the treatment of metastatic colorectal carcinoma and hepatocellular carcinoma [10].…”
Section: Introductionmentioning
confidence: 99%